Development of a New Modeling Circuit for the Remote Terminal Unit (RTU) with GSM Communication - Ab Ghani, Mohd Ruddin; Wan Hassan, Wan Ahmas Redhauddin; Mat Hanafiah, Mohd Ariff; Raman, Siti Hajar (2013)
This paper introduces the design and development of Intelligent Remote Terminal Unit (RTU) which is to be applied as an automation technique for operating and controlling the low voltage (LV) downstream of 415/240V to enhance reliability of power for the consumers. The design proposed based on Global System for Mobile (GSM) communication and this paper also presents as efficient design for distribution automation system and its implementation in remote/automatic monitoring and controlling of the relays (circuit breaker) by means of GSM Short Message Service (SMS) services, automatic decision making and continuous monitoring of distribution system components in real time. The system has been equipped with microcontroller as a main component which act as an RTU programmed using Microcontroller PRO compiler software. The RTU provides monitoring fault operation, controlling functions and data collection for analysis. RTU will initiate the transaction with the digital and output modules. The master of this system is RTU and the slaves are digital and output modules. RTU plays an important role in detecting fault and assigned to serve message immediately in the control room. This system involves the detection of fault connected to the microcontroller(PIC18F77A) and GSM modem. When the fault occurs, the sensor will send the signals to the PIC16F77A. The PIC is programmed to process the data and send the signals to the GSM modem. Once received the data, GSM will send the message to the control room operators or other authorized personnel to alert them on the current situation through cellular phone. The results are then communicated between hardware circuit and simulation circuit for the final conclusion with the properly functional algorithm.